2011
DOI: 10.4297/najms.2011.3367
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic effect of bacteriocin against urinary catheter associated Pseudomonas aeruginosa biofilm

Abstract: Context:Pseudomonas aeruginosa is a gram negative opportunistic bacteria causes several infections commonly colonize these devices and developing biofilms. Bacteria in biofilm can be up to 1,000 times more resistant to antibiotics than the same bacteria circulating in a planktonic state.Case Report:A total of 10 isolates of Pseudomonas aeruginosa were isolated from catheter associated urinary tract infections. While carbenicillin was the most effective antibiotic, all isolates developed multidrug resistant. Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 19 publications
1
24
0
Order By: Relevance
“…As such, we suggest that this antagonistic interaction between K. ornithinolytica and K. terrigena species might result from the synthesis of some antagonistic compounds such as bacteriocins. It is literally known that, bacteriocins are antimicrobial proteins formed by interspecies in order to affect the permeability and instability of cell membrane and eliminate the bacterial strain in the culture or to mediate the dynamics of microbial population (Hetz et al, 2002;Al-Mathkhury et al, 2011). Confirming all these, in our study biofilm formation in K. ornithinolytica's might have been affected by the antagonistic compounds such as bacteriocins, synthesized by K. terrigena (Fig.…”
Section: Discussionsupporting
confidence: 71%
“…As such, we suggest that this antagonistic interaction between K. ornithinolytica and K. terrigena species might result from the synthesis of some antagonistic compounds such as bacteriocins. It is literally known that, bacteriocins are antimicrobial proteins formed by interspecies in order to affect the permeability and instability of cell membrane and eliminate the bacterial strain in the culture or to mediate the dynamics of microbial population (Hetz et al, 2002;Al-Mathkhury et al, 2011). Confirming all these, in our study biofilm formation in K. ornithinolytica's might have been affected by the antagonistic compounds such as bacteriocins, synthesized by K. terrigena (Fig.…”
Section: Discussionsupporting
confidence: 71%
“…Lactobacilli in particular, are regarded to be generally safe and recognized as potent interfering bacteria. Lactobacilli and their derived substances have been used widely in both clinical and experimental trials to inhibit growth of other bacteria on various natural and artificial surfaces, including urinary catheters (Reid and Tieszer, 1994;Reid and Burton, 2002;Reid and Bruce, 2006;Maldonando et al, 2007;Ruiz et al, 2009;Barrons and Tassone, 2008;Fracchia et al, 2010;Ray, 2011;Al-Mathkhury et al, 2011;Sambanthamoorthy et al, 2014;Abd-Alkareem, 2014). In this study, L. acidophilus was isolated from HVS of a healthy female.…”
Section: Discussionmentioning
confidence: 99%
“…The daily incidence of bacteriuria in catheterized patients is approximately 3-10% and among patients with bacteriuria, up to 25% will develop symptoms of local UTI, while about 3% will develop bacteremia (Saint et al, 2005). Studies have also shown that the duration of catheterization is the important factor of bacteriuria (Stickler, 2008;Al-Mathkhury et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Biofilm formation on urinary catheter was investigated using the methods of Victoria and Tajudeen (2011) and Al-Mathkhury et al,, (2011) with some modifications. Foley catheter was cut into 1 cm pieces and placed in 20 mL of NB and artificial urine containing test cultures to a final cell density of 1.5 x 10 8 CFU/mL.…”
Section: Urinary Catheter Biofilm Production Assaymentioning
confidence: 99%
“…Urinary catheters are tubular latex or silicone devices, which when inserted may readily acquire biofilms on the inner or outer surfaces (Al-Mathkhury et al,, 2011). According to Stickler and Zimakoff (1994), a common complication in the care of patients undergoing long-term indwelling bladder catheterization is encrustation and blockage of the catheter.…”
Section: Introductionmentioning
confidence: 99%